Sustainable Development Goals The Impact of Sustainability Measures on Wellbeing - Sharma, Ridhima (Emerald Publishing Limited, 2024)
We need sustainable solutions that can protect our water, energy and food resources while also aiming for zero waste. Sustainable Development Goalsintroduces the subject of sustainable development, delving into detail of the framework to address gaps and shortages in different disciplines and sectors
Description based on publisher supplied metadata and other sources
Keywords: Nachhaltigkeit; Entwicklung